2006
DOI: 10.1021/jo0608467
|View full text |Cite
|
Sign up to set email alerts
|

Aza-β3-Cyclohexapeptides:  Pseudopeptidic Macrocycles with Interesting Conformational and Configurational Properties Slow Pyramidal Nitrogen Inversion in 24-Membered Rings!

Abstract: Among pseudopeptidic foldamers, aza-beta3-peptides have the unique property to possess nitrogen stereocenters instead of carbon stereocenters. As the result of pyramidal inversion at N(alpha)-atoms along the backbone, they behave as a set of C8-based secondary structures in equilibrium. This structural modulation is exploited here to prepare 24-membered macrocycles with great efficiency. Both crystal structures and spectroscopic data establish that aza-beta3-cyclohexapeptides adopt a highly organized conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 66 publications
6
38
0
Order By: Relevance
“…Indeed the N α atom of the azaPhe (i + 2) residue showed a slight pyramidal character with a distance of 0.202 Å from the plane and it has d ‐configuration, whereas the N α atom of the azaPhe (i + 5) residue also shows a pyramidal character but with l ‐configuration and is located out of the plane by 0.232 Å. This inversion of configuration may be a result of interconversion from intramolecular to intermolecular hydrogen bonding with increases in concentration, which has been already observed in literature, and we will discuss this later in this paper . Moreover, X‐ray diffraction experiments revealed that the interatomic distance between the polar sites (NH i+3 ··· O i ) is 2.83 Å, which is an adequate value for intramolecular hydrogen bond interaction by leading to the formation of pseudocycle of 10 atoms between the (CO i ) Ala and (NH i+3 ) Ala from the type (i + 3→i) as shown in Figure (see Supporting Information, Table S2).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Indeed the N α atom of the azaPhe (i + 2) residue showed a slight pyramidal character with a distance of 0.202 Å from the plane and it has d ‐configuration, whereas the N α atom of the azaPhe (i + 5) residue also shows a pyramidal character but with l ‐configuration and is located out of the plane by 0.232 Å. This inversion of configuration may be a result of interconversion from intramolecular to intermolecular hydrogen bonding with increases in concentration, which has been already observed in literature, and we will discuss this later in this paper . Moreover, X‐ray diffraction experiments revealed that the interatomic distance between the polar sites (NH i+3 ··· O i ) is 2.83 Å, which is an adequate value for intramolecular hydrogen bond interaction by leading to the formation of pseudocycle of 10 atoms between the (CO i ) Ala and (NH i+3 ) Ala from the type (i + 3→i) as shown in Figure (see Supporting Information, Table S2).…”
Section: Resultssupporting
confidence: 66%
“…This inversion of configuration may be a result of interconversion from intramolecular to intermolecular hydrogen bonding with increases in concentration, which has been already observed in literature, and we will discuss this later in this paper. [16] More-over, X-ray diffraction experiments revealed that the interatomic distance between the polar sites (NH i+3 ···O i ) is 2.83 Å, which is an adequate value for intramolecular hydrogen bond interaction [17] by leading to the formation of pseudocycle of 10 atoms between the (CO i ) Ala and (NH i+3 ) Ala from the type (i + 3→i) as shown in Figure 1 (see Supporting Information, Table S2). In addition, the distance between C α of residues (i) and (i + 3) of the pseudocycle is less than 7 Å, which supports the existence of -turn conformation.…”
Section: Resultsmentioning
confidence: 99%
“…Quantum chemical calculations carried out on b-3-aza-peptides reveal the presence of a wide variety of secondary structures [85]. Experimental studies with linear or macrocyclic oligomers of N 1 -substituted hydrazinoacetic acid (b 3 -3-aza peptides) showed remarkable conformations, the presence of hydrazino turns, and foldamer behavior [86][87][88][89]. …”
Section: The Coànànàcàcoành Fragment Is a Turn Inducer In Pseudopeptidesmentioning
confidence: 99%
“…Activation of acids using carbodiimides allows the acylation of hydrazino acetic derivatives 94 (R 1 ¼ H) in fair to very good yields, in solution-phase synthesis (entries 1-3) [43,49,84,87] and in solid-phase synthesis (entry 4) [70]. Activation of acids using carbodiimides allows the acylation of hydrazino acetic derivatives 94 (R 1 ¼ H) in fair to very good yields, in solution-phase synthesis (entries 1-3) [43,49,84,87] and in solid-phase synthesis (entry 4) [70].…”
Section: Reaction Of N 1 -Substituted A-hydrazino Acid Derivatives Wimentioning
confidence: 99%
See 1 more Smart Citation